Caracterização de voçorocas em bordas de relevo residual tabular em Quirinópolis - Sousa, Alik Timóteo de (2010)
The city of Quirinópolis, which is located in the Southwest part of Goiás State, in the Basin of Paranaíba River, is consisted by smoothed reliefs containing residual tabular hills whose altitudes range from 370 to 880m. The “Serra da Confusão do Rio Preto”, located in the center part of the city, is representative on the local landscape. In the highest parts of this hill there are many erosive foci, which are of a huge size, especially of gullies type and mainly near of its south edge, where it is developed a big dissected recess containing several headwaters drainage. Two gullies were selected for detailed studies because they are in the same geomorphological situation of a concave edge of a residual relief, however, related to different systems of soil, one on a pedological cover represented by a Red Dusky Soil, Plinthosol petroferric and Gley soil and one on PSAMENT and Histosols . The study aimed to identify the source, the constraints and the evolution of the processes that caused the emergence and evolution of gullies to devise proposals for stabilization and / or appropriate control. Five interviews were carried out with former residents of the hill about the origin and evolution of the selected gullies. Subsequently, thematic maps were produced in the physical environment of use and occupation of the research area and as a source, satellite images Landsat TM (60 m resolution) 1980 and Landsat TM5 (30 m resolution) and SRTM images in 2008, to observe the evolution of land uses and gullies throughout this period. The operational capabilities of the software used were: Envi 4.3, Arc Map - ArcGIS 9.2, Spring 5.0 and CorelDRAW X3 version 13. Then, the entries were drawn erosive events according to the methodology of the IPT. Later on, they were described the horizons of exposed soil on the slopes of gullies in toposequence, with the use of rappelling. The physico-hydric soil characteristics were obtained from field tests of resistance to penetration with an impact penetrometer, saturated hydraulic conductivity using the Guelph permeameter, followed by the characterization of the physical attributes (water content, texture, density particles and soil total porosity, macro and micro) and chemical (pH, OM, Fe, P, K, Ca, Mg, H + Al, Al, CEC and V). Analyses were performed by ANOVA and Tukey test at 5% of probability for the comparison of means. The results showed that the gully of “Córrego do Andre” is developing on old scar erosive, as evidenced by the identification of horizons and / or different soil layers between the right and left slope erosion that probably were deposited by successive cuts and fills. Its evolution is driven by surface flows concentrated on cattle trails that surround it, associated with concentrated flows that spill over the terraces and reach their borders, as well as through the exfiltration of subsurface water in contact horizons Bw Bc or with C underlying the slopes strongly inclined. The Ting gully soils with lower clay in its upper reaches, has low penetration resistance (compaction) and high hydraulic conductivity, so the progression is linked to performance continues the erosion mechanisms represented by the internal pipings. The superficial runoff contributes little to the progression of this erosion.